Objektivitas Berita di Harian Kompas dan Kompas.Com - Halimatul Abkoriyah; Tribuana Tungga Dewi (CoverAge: Journal of Strategic Communication, 2017)
Previous studies showed the objectivity of news in print media and online media are different. Print media frequently mentioned as more objective on its news coverage than the online media. This article purpose is to identify and compare news objectivity of Harian Kompas and Kompas.com on covering the murder of Engeline in Bali. By using quantitative content analysis, we found that both Harian Kompas and Kompas.com have not present fully objective coverage in this case. Nevertheless, Harian Kompas can be more presenting the news objectively compare to Kompas.com. This might happen though both media companies owned by the sama media group, but it runs by different management team and also there are some differences on its media output characteristics.